A comparative analysis of the advantages and disadvantages of blended learning and traditional teaching in a multidisciplinary context - Ren, Wenxuan; Wang, Rui; Zhao, Xiaoyan; Shi, Jingjing (Frontiers in Education, 2025)
This study examines the evolution of blended learning in China, anchored in Massive Open Online Courses (MOOCs) and Small Private Online Courses (SPOCs), and evaluates its effects on teaching quality, ethics education, and student satisfaction. Combining literature review and quantitative analysis, the research demonstrates that blended learning surpasses traditional pedagogy across these three dimensions—a finding further validated through follow-up interviews. However, students identified notable limitations, including a tendency for online content to foster passive learning and challenges for instructors in classroom management. To address these issues, the paper proposes that educators prioritize content coherence in course design and incorporate student feedback on platform usability to optimize both pedagogical effectiveness and learning outcomes. Future studies should investigate the cost-efficacy of blended learning, specifically its capacity to sustain or elevate educational standards with reduced instructional resources.